High-Throughput Field Phenotyping Traits of Grain Yield Formation and Nitrogen Use Efficiency: Optimizing the Selection of Vegetation Indices and Growth Stages - Prey, Lukas; Hu, Yuncai; Schmidhalter, Urs (Frontiers in Plant Science, 2020)
High-throughput, non-invasive phenotyping is promising for evaluating crop nitrogen use efficiency (NUE) and grain yield (GY) formation under field conditions but its application for genotypes differing in morphology and phenology is still rarely addressed. This study therefore evaluates the spectral estimation of forty-five dry matter (DM) and N traits, related to GY and grain N uptake (Nup) in high-yielding winter wheat breeding lines. From 2015–2017, hyperspectral canopy measurements were acquired on 26 measurement dates during vegetative and reproductive growth and 48 vegetation indices from the visible (VIS), red edge (RE) and near infrared (NIR) spectrum were tested in linear regressions for assessing the influence of measurement stage and index selection. For most traits including GY and grain Nup, measurements at milk ripeness were the most reliable. Coefficients of determination (R²) were generally higher for traits related to maturity than for those related to anthesis canopy status. For GY (R² = 0.26***–0.51*** in the three years), and most DM traits, indices related to the water absorption band at 970 nm provided better relationships than the NIR/VIS indices, including the NDVI, and the VIS indices. In addition, most indices including RE bands, notably NIR/RE combinations, ranked above the NIR/VIS group. Due to index saturation, the index differentiation was most apparent in the highest-yielding year. For grain Nup and total Nup, the RE/VIS index MSR_705_445 and the simple ratio R780_740 ranked highest, followed by several other RE-indices. Among the vegetative organs, R²-values were mostly highest and lowest for leaf and spike traits respectively. Moderate, yet year-dependent relationships were obtained from RE-indices for the N harvest index, N translocation and its efficiency. The results suggest the use of sensor-based phenotyping as a useful support-tool for screening of yield potential and NUE and for identifying contributing plant traits—which, due to their expensive and cumbersome destructive determination are otherwise not readily available—both from an organ-level and temporal perspective. Depending on the available sensors, water bands and RE bands should be preferred over NIR/VIS indices for DM traits and N-related traits, respectively, and milk ripeness is suggested as the most reliable stage.